Anticoagulation effect of estroprogesterone therapy in women in menopausal period - Jastrzębska, Maria; Sankowski, Zbigniew; Stanosz, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2005)
Natural hormones enrolled in 35 women at estro-progesteronic therapy on coagulation system. The scientific work showed, that transdermal hormone therapy is not disturbing physiological balance in coagulation system.